Make: Electronics - Platt, Charles, ....- (San Francisco : Maker Media, 2015)
Completely re-written with most photos and schematics replaced and updated, this new iteration of Charles Platt's seminal beginner's guide to electronics continues the "learning through discovery" model for which it has been praised since the text was first published in 2009. Single-bus breadboards are now used throughout, diagrams rather than photographs show circuit placement, internal circuit illustrations have been redrawn for clarity, and an expanded focus on Arduino as the most popular microcontroller distinguish this second edition—as does a layout more friendly to mobile reading. Unchanged are the dry humor and clear explanations that have made this a best-selling book for six years and counting. Get ready to burn things out and mess things up—because that's how you learn!
At head of title: Make:.
Includes index.
Previous edition: Beijing: O'Reilly, 2009.
Keywords: Electronic apparatus and appliances -- Design and construction -- Amateurs' manuals